AN ANALYSIS OF STUDENTS' GRAMMAR KNOWLEDGE IN PRODUCING PROCEDURE TEXT ORALLY AT SMK N 9 PADANG - Abdullah Zaid; Aryuliva Adnan; Don Narius (Journal of English Language Teaching, 2018)
This research aims to discover SMK students’ ability in using grammar, especially sentence structures, in producing oral procedure text. The design of this research was descriptive research. The population was 125 grade twelve students majoring in the food and beverage service study program at SMKN 9 Padang who were divided into 6 classes: XII JB 1, XII JB 2, XII JB 3, XII JB 4, XII Ps 1 and XII Ps 2. The sample was obtained by using random cluster sampling technique which resulted in XII Ps 1 class which had 28 students. The data were collected by giving them a speaking test to produce oral procedure text. The result showed that students’ ability in using declarative sentence in producing oral procedure text was in poor level (85,71%). Meanwhile, students’ ability in using imperative sentence in producing oral procedure text was in good level (46,43%).